THE INFLUENCE OF INCOME, ACCOUNTABILITY, AND TRANSPARENCY ON THE CILEUNGSI COMMUNITY'S INTEREST IN PAYING ZAKAT THROUGH KITABISA.COM - Shofura Muroqobatullah; R. Mohd. Zamzami (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to determine the effect of income, accountability and transparency in the Cileungsi citizen intention of paying zakat through Kitabisa.com. Population in this research is all Cileungsi citizen with the sample is 400 people. This research uses quantitative method and uses primer data. From this research independent variable income (X1) positively and significantly affect the intention of paying zakat through Kitabisa.com, independent variable accountability (X2) has positively and significantly affected the intention of paying zakat through Kitabisa.com, and the last independent variable transparency (X3) has positively and significantly affected the intention of paying zakat through Kitabisa.com. Simultaneously the results show that the variables of income, accountability and transparency affect interest and affect the interest dependent variable in paying zakat through Kitabisa.com about 46.8%.